2022
DOI: 10.3390/biomedicines10092099
|View full text |Cite
|
Sign up to set email alerts
|

The Brave New World of Early Treatment of Multiple Sclerosis: Using the Molecular Biomarkers CXCL13 and Neurofilament Light to Optimize Immunotherapy

Abstract: Multiple sclerosis (MS) is a highly heterogeneous disease involving a combination of inflammation, demyelination, and CNS injury. It is the leading cause of non-traumatic neurological disability in younger people. There is no cure, but treatments in the form of immunomodulatory drugs (IMDs) are available. Experience over the last 30 years has shown that IMDs, also sometimes called disease-modifying therapies, are effective in downregulating neuroinflammatory activity. However, there are a number of negatives i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 141 publications
0
8
0
Order By: Relevance
“…Our study aimed to examine the therapeutic potential of boswellic acid in EAE mice, as a widely accepted animal model for MS [31]. MS has no cure, and current medicines are only partially effective and have side effects [32]. Hence consequently, there is an urgent need to discover innovative and safe medicines capable of modulating the immune system, protecting the CNS, and promoting remyelination.…”
Section: Discussionmentioning
confidence: 99%
“…Our study aimed to examine the therapeutic potential of boswellic acid in EAE mice, as a widely accepted animal model for MS [31]. MS has no cure, and current medicines are only partially effective and have side effects [32]. Hence consequently, there is an urgent need to discover innovative and safe medicines capable of modulating the immune system, protecting the CNS, and promoting remyelination.…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis and treatment are crucial, and immunotherapy using immunomodulatory drugs (IMDs) is currently the primary approach to slow its progression ( Frau et al, 2018 ; Pachner, 2022 ). In recent years, the application of artificial intelligence (AI) in healthcare ( Davenport and Kalakota, 2019 ) has shown significant potential, particularly in the analysis of medical images created by MRI.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…It was also found that by combining the CXCL13 index with the CSF NfL score, predictive values can be further maximized ( Pachner, 2022 ). Among the 67 patients with MS, 41 demonstrated an initial clinical demyelinating event (ICDE), which is an early signal to apply immunomodulatory therapy.…”
Section: Potential Biochemical Neurodegeneration Markers Associated W...mentioning
confidence: 99%
“…Otherwise, CXCL13 has been found to increase significantly in MS patients compared to a CIS group ( Khademi et al, 2011 ). Such inconsistencies may be due to some studies not employing optimal analytical techniques; while most studies have been based on ELISA, more accurate results have been achieved using Luminex, SIMOA or immuno-PCR have been proven to provide more sensitive results in CXCL13 detection ( Pachner, 2022 ).…”
Section: Potential Biochemical Neurodegeneration Markers Associated W...mentioning
confidence: 99%